TINDAK TUTUR DIREKTIF DAN KOMISIF DALAM FILM MAK KELAPON KARYA ADRI ADDAYUNI - Wardany, Elize; Patriantoro, Patriantoro; Heryana, Nanang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractSpeech acts are a part that can not be separated from a story. Speech can support a plot in a story. The plot used in the story can be found from the narrator's speech or speech used by the characters in the story. The issues discussed in the research are the types and context of the reciprocal and commercially directive acts in Mak Kelapon film. Methods in this study include data collection techniques and data analysis techniques. The form of research in this study is a form of qualitative research. Data collection techniques used in this study, the method of referring to the technique of listening to spirited  data with documents. The results of the analysis of speech acts directive and commisive in Film Mak Kelapon Karya Adri Addayuni is divided into two speech acts. The first act of speech acknowledgment consists of 6 types include type 1 amounted to 20, type 2 amounted to 56, type 3 amounted to 10, type 4 amounted to 4, type 5 amounted to 3, type 6 amounted to 4. While commissive speech acts consist of 2 types including type 7 amounted to 13 and type 8 amounted to 7.Keywords: act directive and comic speech, film dialogue, Mak Kelapon Karya Adri Addayuni.